CUMULATIVE CARDIO-VASCULAR RISK IN HYPERTENSIVE PATIENTS: EFFECTS OF ANGIOTENSIN CONVERTING ENZYME INHIBITORS - L. I. Katelnitskaya; L. A. Haisheva; S. E. Glova (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To assess cumulative cardio-vascular (CV) risk and elasticity of big-to-middle size arteries in hypertensive patients depending on age, sex and enalapril (Enap, Dr. Reddy’s) effects on these features. Material and methods. 143 patients with arterial hypertension of 1-2 stages were split in 3 groups: 1st – patients younger than 55 y.o. (17 men, 27 women before menopause); 2nd – patients aged 55-65 y.o. (16 men, 38 women); 3rd – elder than 65 y.o. (11 men, 34 women). Fatal CV risk according to SCORE scale and cumulative risk of acute coronary disease (CAD) events according to PRCAM program was assessed before and after 4 weeks of enalapril therapy (5-30 mg/d). Besides the speed of pulse wave spread (SPWS) was determined by method of volume sphygmography. Results. Normal SPWS in elastic arteries was observed in women under 55 y.o. SPWS disturbances were detected in elderly patients. Lower blood pressure (BP) levels and better plasma lipid profile was found in women of young and middle age in comparison with these in men of the same age. More than 80% of hypertensive patients have high CV risk, especially in elderly ones. Enam improved SPWS in elastic arteries, reduced BP and cumulative CV risk. Conclusion. There are gender and age differences between BP levels, SPWS indices, plasma lipid profiles and cumulative CV risks in hypertensive patients. Enalapril improves these characteristics.